Photothermal and thermal response release antibacterial film as well as preparation method and application thereof
The photothermal and thermal response antibacterial film addresses issues of uneven heating and volatile release in existing technologies by combining natural plant essential oils with silica-coated nanoparticles for comprehensive and sustained antibacterial protection.
Patent Information
- Application Number
- CN202411249408.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-06
AI Technical Summary
Existing antibacterial food packaging technologies face challenges with release-type agents like natural plant essential oils, which are volatile and difficult to control, and contact-type photothermal sterilization, which struggles with uneven heating and coverage of irregularly shaped foods.
A photothermal and thermal response release antibacterial film combining natural plant essential oil inclusion compounds with photothermal conversion nanoparticles, coated with a silica shell to enhance stability and distribution, achieving synergistic sterilization through both contact and release mechanisms.
The film provides efficient, broad-spectrum bactericidal effects by rapidly killing bacteria upon initial irradiation and sustaining antibacterial activity over time, ensuring complete food coverage and extended shelf life with improved nanomaterial stability and biocompatibility.
Smart Images

Figure CN119119661A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of functional packaging technology, and in particular to a photothermal and thermal response releasing antibacterial film and a preparation method and application thereof. Background Art
[0002] With the development of society and the progress of life, people have higher and higher requirements for food, especially food preservation has become a key issue of concern to people. The primary issue of food preservation is food spoilage. During the storage of food, microorganisms remaining on the surface of food will accelerate the spoilage of food. To address the problem of microorganisms accelerating food spoilage, a simple and effective method commonly used in the prior art is to give food packaging antibacterial properties, thereby extending the shelf life of food.
[0003] At present, adding antimicrobial agents to packaging by physical or chemical methods is an effective way to give packaging antimicrobial properties; conventional antimicrobial methods are generally divided into two types, namely release type and contact type. The release type mainly adds some active substances as antimicrobial agents to the packaging, and then during the storage of food, the active substances will slowly release from the packaging to inhibit the growth of residual colonies on the food, thereby effectively extending the shelf life of the food; natural plant essential oils are often added to the packaging as active substances to prepare antimicrobial fresh-keeping packaging due to their own pure natural and good antimicrobial effects; although natural plant essential oils have the advantages of pure natural and good antimicrobial effects, they are extremely volatile and often diffuse in large quantities at the beginning of storage, and cannot play a long-term and continuous antibacterial effect. If the essential oil is embedded, although the problem of large-scale release of essential oils is solved, the release of essential oils is also limited to a certain extent. The release efficiency of essential oils cannot be accurately controlled, resulting in the release of essential oils insufficient to achieve the ideal antibacterial effect. In addition, most natural plant essential oil release-type antimicrobial agents have very different antibacterial effects on different types of bacteria, and a single type of plant essential oil cannot achieve a broad-spectrum bactericidal effect.
[0004] In addition to natural plant essential oils, release-type antibacterials also use metal ions such as silver, manganese, copper, and iron as antibacterial agents. These metal ions react with proteins, phospholipids and other components on the cell membrane, destroying the integrity of the cell membrane and causing the cells to lose their selective permeability, thereby leading to bacterial death. Although metal ions have a good bactericidal effect on bacteria, they also pose major food safety issues. Among them, the control of the amount of metal ions added is a key issue. If the amount of metal ions added is too little, the bactericidal effect will not be significant. If the amount of metal ions added is too large, excess metal ions will migrate to the food in large quantities, causing major food safety issues.
[0005] The most representative contact sterilization is photothermal sterilization, which is to mix materials with photothermal conversion properties into packaging and release them in the form of heat energy under the irradiation of light of a specific wavelength. It destroys the cell membrane and denatures the protein at high temperature, causing bacterial cell death. It has the advantages of being easy to use, highly efficient, and having broad-spectrum antibacterial activity, and is a powerful antibacterial strategy. However, photothermal contact sterilization also has the following disadvantages: First, contact sterilization can only be achieved when the packaging contacts the food, and most foods on the market are irregular in shape. Although there are ways to make the packaging fit tightly with the food in the existing technology, it is still difficult to ensure that the packaging covers all parts of the food without dead ends, making it difficult for contact sterilization to sterilize the food in all directions. Second, most of the photothermal materials currently used are nanomaterials with photothermal conversion properties. The photothermal conversion properties are given to the packaging by doping the nanomaterials into the packaging. However, nanomaterials often agglomerate due to their small size and electrostatic effects between each other. Once aggregation occurs, it will affect the dispersion of the nanomaterials in the packaging. If the dispersion is uneven, it will lead to uneven photothermal heating, which will seriously affect the effect of photothermal sterilization.
[0006] In summary, since both release-type and contact-type antibacterial agents have obvious shortcomings, the application of antibacterial packaging in actual production is greatly limited. Therefore, the development of a packaging that can make up for the shortcomings of release-type and contact-type antibacterial agents and has a high-efficiency antibacterial effect is of great significance to the development of antibacterial food packaging. Summary of the invention
[0007] The purpose of the present invention is to provide a photothermal and thermal response release antibacterial film and its preparation method and application to solve the problems existing in the above-mentioned prior art. The antibacterial film provided by the present invention combines contact photothermal sterilization with release-type active substance sustained-release antibacterial. In the early stage of preservation, the active substance is quickly released through high temperature and thermal response to kill all bacteria on the food. During the subsequent food storage period, the active substance will be slowly and continuously released to achieve a long-term antibacterial effect.
[0008] To achieve the above object, the present invention provides the following solutions:
[0009] One of the technical solutions of the present invention is a photothermal and heat-responsive antibacterial film, the raw materials include a solvent, and the following components in the mass percentage of the solvent: 1-10% of the film-forming substrate, 0.5-3% of the natural plant essential oil inclusion compound, 0.001-4% of the photothermal conversion substance, and 0-0.6% of glycerol. That is, based on the mass of the solvent, the amounts of the film-forming substrate, the natural plant essential oil inclusion compound, the photothermal conversion substance, and the glycerol are 1-10%, 0.5-3%, 0.001-4%, and 0-0.6% of the solute mass, respectively.
[0010] Preferably, the photothermal and heat-responsive antibacterial film comprises a solvent and the following components in amounts as percentages of the solvent by mass: 10% of a film-forming substrate, 1% of a natural plant essential oil inclusion compound, and 0.0027% of a photothermal conversion substance.
[0011] Furthermore, the film-forming substrate is one or more of polyvinyl alcohol (PVA), chitosan, carboxymethyl cellulose, polylactic acid and pectin.
[0012] Furthermore, when the film-forming substrate is pectin and / or chitosan, the amount of glycerol used is not zero.
[0013] Furthermore, the natural plant essential oil inclusion compound is composed of natural plant essential oil and cyclodextrin, and can be called a natural plant essential oil cyclodextrin inclusion compound. The natural plant essential oil cyclodextrin inclusion compound is substantially a microcapsule structure, and the natural plant essential oil is embedded in the microcapsule to improve the stability and release efficiency of the natural plant essential oil in the film.
[0014] Furthermore, the natural plant essential oil is one or more of cinnamon essential oil, thymol essential oil, oregano essential oil, eugenol essential oil, neroli essential oil, peppermint essential oil and tea tree essential oil.
[0015] Furthermore, the natural plant essential oil is preferably cinnamon essential oil.
[0016] Furthermore, the cyclodextrin is preferably β-cyclodextrin.
[0017] Cyclodextrin also has good stability at high temperatures and is not easily affected by temperature changes. Choosing cyclodextrin to prepare natural plant essential oil inclusion compounds can keep the inclusion compounds stable in high temperature environments. If starch or protein and other substances are used as microcapsules to embed essential oils, they are easily affected by temperature changes and denatured, resulting in the release of all the essential oils and the loss of the sustained-release effect.
[0018] Furthermore, the photothermal conversion material is nanoparticles.
[0019] Furthermore, the photothermal conversion material is one or more of gold nanoparticles, silver nanoparticles, manganese oxide nanoparticles and lignin nanoparticles.
[0020] Furthermore, the photothermal conversion material is preferably gold nanoparticles.
[0021] Furthermore, the surface of the photothermal conversion material is coated with a silica shell, that is, the gold nanoparticles, silver nanoparticles, manganese oxide nanoparticles and lignin nanoparticles are specifically gold core silica shell core-shell nanoparticles, silver core silica shell core-shell nanoparticles, manganese oxide core silica shell core-shell nanoparticles and lignin core silica shell core-shell nanoparticles with a silica shell on the surface. The above-mentioned core-shell nanoparticles are obtained by coating a layer of silica shell on the surface of nanoparticles through surface modification. Since the stability of nanoparticles in the reaction solution is poor and they are prone to agglomeration, a layer of silica shell is coated on the surface to improve the stability of the nanoparticles in the reaction system, to avoid aggregation and precipitation during the mixing reaction with the film-forming substrate, so that the nanoparticles are unevenly distributed during the final film formation, resulting in uneven photothermal temperature at various positions on the film, which greatly affects the photothermal conversion efficiency of the film.
[0022] Furthermore, the thickness of the silicon dioxide shell layer is 15 nm.
[0023] Furthermore, the surface coating of the silica shell layer is performed by adding 3-aminopropyltrimethoxysilane solution to the nanoparticle aqueous solution, stirring at room temperature for 10 minutes, then adding sodium metasilicate solution and continuing to stir for more than 3 minutes, and finally condensing and refluxing at 90° C. for 2 hours.
[0024] Furthermore, the concentration of the 3-aminopropyltrimethoxysilane is 1 mM; the concentration of the sodium metasilicate solution is 0.54 wt % based on SiO2, and the pH of the sodium metasilicate solution is adjusted to 9.5-11 with HCl.
[0025] Furthermore, the volume ratio of the nanoparticle aqueous solution, the 3-aminopropyltrimethoxysilane solution and the sodium metasilicate solution is 30:0.4:5.
[0026] Further, when the nanoparticle aqueous solution is a manganese oxide nanoparticle aqueous solution or a lignin nanoparticle aqueous solution, the concentration of the nanoparticle aqueous solution is 4 mg / 30 mL;
[0027] When the nanoparticle aqueous solution is a gold nanoparticle (AuNPs) aqueous solution, the preparation method is as follows: first, 1wt% HAuCl4 solution is added to water at a volume ratio of 1:99, heated to boiling at 125°C, then 0.7vol% sodium citrate solution is added, and condensation reflux reaction is performed for 10 minutes to obtain an AuNPs aqueous solution; the concentration of the sodium citrate solution is 25.4mM;
[0028] When the nanoparticle aqueous solution is a silver nanoparticle aqueous solution, its preparation method is: first dissolve silver nitrate in water, heat to boiling under stirring, then add sodium citrate solution dropwise, and continue to react for 1.5 hours to obtain the silver nanoparticle aqueous solution; the concentration of the sodium citrate solution is 38.8mmol / L, and the dosage ratio of the silver nitrate, water and sodium citrate solution is 9mg:49mL:1mL.
[0029] Furthermore, the solvent is one or more of water, acetic acid and dichloromethane.
[0030] Technical solution 2 of the present invention: The method for preparing the above-mentioned photothermal and thermal response release antibacterial film comprises the following steps:
[0031] Weigh each raw material according to the mass percentage composition of the raw materials, mix the other raw materials except the natural plant essential oil inclusion compound to obtain a composite solution; add the natural plant essential oil inclusion compound to the composite solution to obtain a film-forming liquid; pour the film-forming liquid into a vessel for film formation, dry it, and obtain the photothermal and thermal response release antibacterial film.
[0032] Further, according to different selected raw materials, the step of mixing other raw materials except the natural plant essential oil inclusion compound to obtain a composite solution; and adding the natural plant essential oil inclusion compound to the composite solution to obtain a film-forming solution specifically selects one of the following methods:
[0033] Method 1: Take a portion of the solvent and mix it with the photothermal conversion material to obtain a photothermal conversion material solution; mix the film-forming substrate, the photothermal conversion material solution and the remaining solvent, heat and stir at 75-90° C. for 2-3 hours to obtain a composite solution; cool the composite solution to 50-55° C. and then add the natural plant essential oil inclusion compound, continue heating and reacting at 50-55° C. for 0.5 hours to obtain a film-forming solution (when the film-forming substrate is only PVA and no additional plasticizer glycerol is needed, method 1 is selected);
[0034] Method 2: Mix a portion of the solvent with the photothermal conversion substance to obtain a photothermal conversion substance solution; mix the film-forming substrate, the photothermal conversion substance solution and the remaining solvent, heat and stir at 75-90° C. for 2-3 hours, then add glycerol, continue heating and stirring for 2-3 hours to obtain a composite solution; cool the composite solution to 50-55° C., add the natural plant essential oil inclusion compound, continue heating and reacting at 50-55° C. for 0.5 hours, and obtain a film-forming solution (when the film-forming substrate is only pectin and plasticizer glycerol needs to be added, method 2 is selected);
[0035] Method 3: taking a portion of the solvent and mixing it with the photothermal conversion material to obtain a photothermal conversion material solution; mixing the film-forming substrate, the photothermal conversion material solution, glycerol and the remaining solvent, stirring at room temperature for 12 hours to obtain a composite solution; adding the natural plant essential oil inclusion compound to the composite solution, continuing to stir the reaction for 0.5 hours, and obtaining a film-forming solution (when the film-forming substrate is only chitosan and the plasticizer glycerol needs to be added, select method 3);
[0036] Method 4: Mix the film-forming substrate, the photothermal conversion substance and the solvent, stir and react at room temperature for 2-3 hours to obtain a composite solution; add the natural plant essential oil inclusion compound to the composite solution, continue stirring and reacting for 0.5 hours to obtain a film-forming solution (when the film-forming substrate is only polylactic acid and no additional plasticizer glycerol is needed, select method 4);
[0037] Method 5: taking a portion of the solvent and mixing it with the photothermal conversion material to obtain a photothermal conversion material solution; mixing the film-forming substrate, the photothermal conversion material solution and the remaining solvent, stirring at room temperature for 0.5 hours to obtain a composite solution; adding the natural plant essential oil inclusion compound to the composite solution, and continuing to stir for 0.5 hours to obtain a film-forming solution (when the film-forming substrate is only carboxymethyl cellulose and no additional plasticizer glycerol is needed, method 5 is selected);
[0038] Method six: Take a part of the solvent and mix it with the photothermal conversion material to obtain a photothermal conversion material solution; take a part of the solvent and mix it with one of the film-forming substrates to obtain a film-forming substrate solution 1; mix the other film-forming substrate with the photothermal conversion substance solution and the remaining solvent to obtain a film-forming substrate solution 2; mix the film-forming solution 1 and the film-forming solution 2 to obtain a composite solution; add the natural plant essential oil inclusion complex to the composite solution, continue stirring for 0.5h, and obtain a film-forming solution (when the film-forming substrate is a composite of two materials, select method six).
[0039] Furthermore, the stirring speed in the method 1 and the method 2 is 700 rpm.
[0040] The third technical solution of the present invention: Application of the above-mentioned photothermal and thermal response release antibacterial film in food packaging.
[0041] Furthermore, the specific operation of the application is: using the photothermal and heat-responsive antibacterial film to seal and package the food, and after the sealing and packaging, irradiating the photothermal and heat-responsive antibacterial film with 808nm near-infrared light for 5 minutes.
[0042] The present invention discloses the following technical effects:
[0043] (1) The present invention prepares a photothermal and heat-responsive release antibacterial film by compounding a photothermal conversion material with a photothermal conversion effect and a natural plant essential oil inclusion compound into a film-forming substrate, thereby realizing a combination of contact sterilization and release sterilization. The antibacterial film can be irradiated with light of a specific wavelength at the initial stage of food storage, so that the film heats up rapidly, and most of the bacteria on the food are killed by a suitable temperature. At the same time, as the temperature rises, the plant essential oil accelerates its diffusion speed from the inclusion compound under the driving force of thermal power, and the release rate is greatly improved. Thus, a double sterilization effect is achieved through the synergistic sterilization of release and contact. The problem that contact sterilization cannot fully cover the food, resulting in poor sterilization efficiency, is solved, and the problem that after the volatile active substance is embedded, the release rate is difficult to control, the release efficiency is low, and the sterilization effect is not ideal is also solved. The advantages of the two sterilization methods are fully utilized, and the problems existing in the two sterilization methods are overcome, thereby greatly improving the antibacterial efficiency of the film.
[0044] (2) In addition to being able to sterilize food through the synergistic effects of release and contact during the initial storage period, the antibacterial film of the present invention also makes it difficult for bacteria in the external environment to enter the interior of the package due to the barrier of the package during the storage period of the food. In addition, the remaining plant essential oil can be continuously and slowly released at room temperature, achieving a continuous antibacterial effect, further extending the shelf life of the food.
[0045] (3) The antibacterial film of the present invention has good bactericidal effect, simple preparation process, small amount of raw materials used, low overall cost, and effectively reduces the amount of antibacterial agent added through release-type and contact-type synergistic bactericidal methods, so that the composite film as a whole has good biocompatibility and meets the requirements of food fresh-keeping packaging. In summary, the antibacterial film of the present invention has great application prospects in the field of food packaging.
[0046] (4) The present invention improves the stability of the nanomaterial in the reaction system by modifying and coating the surface of the nanomaterial with a silica shell layer, so that the nanomaterial can be evenly distributed in the film, thereby solving the problem of uneven distribution of nanoparticles during final film formation, which leads to uneven photothermal temperature, and can effectively improve the packaging photothermal conversion efficiency; in addition, silica also has good biocompatibility, so by coating the silica shell layer, the biocompatibility of the photothermal conversion material can be further improved, thereby improving the safety of the film. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0048] Figure 1 The photothermal conversion temperature diagram of the thin film prepared in Examples 1-6;
[0049] Figure 2 The light-to-heat conversion temperature diagram of the thin films prepared in Examples 7-8 and Comparative Examples 1-3;
[0050] Figure 3 The photothermal conversion temperature diagram of the thin films prepared in Examples 14-16;
[0051] Figure 4 This is the colony image of Staphylococcus aureus in the film antibacterial experiment;
[0052] Figure 5 This is the colony picture of Escherichia coli in the film antibacterial experiment;
[0053] Figure 6 This is the inhibition rate diagram of Staphylococcus aureus in the film antibacterial experiment;
[0054] Figure 7 This is the inhibition rate diagram of Escherichia coli in the film antibacterial experiment;
[0055] Figure 8 It is a line graph of the amount of essential oil released from the film;
[0056] Fig. 9 It is a line graph of the essential oil release rate of the films prepared in Example 3 and Comparative Example 5;
[0057] Fig.10 The colony images of the blank group, control example 1 and control example 2 on the second and fifth days in the beef preservation experiment;
[0058] Fig.11 The colony diagrams of control example 3, control example 4 and embodiment 3 on the second and fifth days in the beef preservation experiment;
[0059] Fig.12 This is a comparison chart of the number of colonies in different groups in the beef preservation experiment on the second and fifth days;
[0060] Fig.13 This is a comparison of TVB-N of different groups in the beef preservation experiment on the second and fifth days. DETAILED DESCRIPTION
[0061] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0062] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0063] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0064] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0065] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0066] The preparation method of the natural plant essential oil β-cyclodextrin inclusion complex used in the following examples and comparative examples is as follows: 9g β-cyclodextrin is dissolved in a mixed solution of 90mL ethanol and deionized water (1:2, v / v), and stirred continuously for 3h at 55±1°C using a magnetic stirrer with a rotation speed of 700rpm to obtain a β-cyclodextrin solution. 1g cinnamon essential oil is dissolved in 10mL ethanol, and slowly added to the β-cyclodextrin solution under continuous stirring, so that the mass ratio of cinnamon essential oil to β-cyclodextrin is 10:90, and the resulting mixed solution is stirred for 2.5h at 50±1°C. After the mixed solution is cooled to room temperature, it is placed in a 4°C environment and frozen overnight. The precipitate is purified by vacuum filtration and rinsed twice with 30vol% ethanol, and then freeze-dried for 12h to obtain a natural plant essential oil β-cyclodextrin inclusion complex dry powder, which is placed in a sealed container and stored at 4°C for subsequent use.
[0067] The preparation method of the gold core silica shell core-shell nanoparticles used in the following examples and comparative examples is as follows: first, 1 mL of 1 wt% HAuCl4 solution is added to 99 mL of deionized water, heated to boiling at 125°C, then 0.7 mL (25.4 mM) sodium citrate solution is added under magnetic stirring at a speed of 700 rpm, and condensed and refluxed for 10 min to obtain an AuNPs aqueous solution. After the AuNPs aqueous solution is cooled to room temperature, 0.4 mL (1 mM) 3-aminopropyltrimethoxysilane solution is added to 30 mL of the AuNPs aqueous solution, stirred at room temperature at a speed of 500 rpm for 10 min, then 5 mL of sodium metasilicate solution (0.54 wt% SiO2, adjusted to pH 10 with HCl) is added and stirred for 10 min, and finally, condensed and refluxed for 2 h at 90°C to obtain a gold core silica shell core-shell nanoparticle aqueous solution, centrifuged, and dried to obtain a solid product.
[0068] The preparation method of the silver core silica shell core-shell nanoparticles used in the following examples is as follows: first, 9 mg of silver nitrate is dissolved in 49 mL of water and heated to boiling under magnetic stirring at a speed of 700 rpm. Then, 1 mL of 38.8 mmol / L sodium citrate solution is added dropwise, and the reaction is continued for one and a half hours to obtain an aqueous solution of silver nanoparticles. After the aqueous solution of silver nanoparticles is cooled to room temperature, 0.4 mL (1 mM) of 3-aminopropyltrimethoxysilane solution is added to 30 mL of the aqueous solution of silver nanoparticles, stirred at room temperature at a speed of 500 rpm for 10 min, then 5 mL of sodium metasilicate solution (0.54 wt% SiO2, adjusted to pH 10 with HCl) is added and stirred for 10 min, and finally, the solution is condensed and refluxed at 90° C. for 2 h to obtain an aqueous solution of silver core silica shell core-shell nanoparticles, centrifuged, and dried to obtain a solid product.
[0069] The preparation method of manganese oxide core silica shell core-shell nanoparticles used in the following examples is as follows: 4 mg of manganese oxide nanoparticles are added to 30 mL of deionized water, stirred evenly, and then 0.4 mL (1 mM) of 3-aminopropyltrimethoxysilane solution is added, and stirred at room temperature at a speed of 500 rpm for 10 min, and then 5 mL of sodium metasilicate solution (0.54 wt% SiO2, adjusted to pH 10 with HCl) is added and continued to stir for 10 min, and finally, condensed and refluxed at 90°C for 2 h to obtain an aqueous solution of manganese oxide core silica shell core-shell nanoparticles, centrifuged, and dried to obtain a solid product.
[0070] The preparation method of the lignin core silica shell core-shell nanoparticles used in the following examples is as follows: 4 mg of lignin nanoparticles are added to 30 mL of deionized water, stirred evenly, and then 0.4 mL (1 mM) of 3-aminopropyltrimethoxysilane solution is added, and stirred at room temperature at a speed of 500 rpm for 10 min, and then 5 mL of sodium metasilicate solution (0.54 wt% SiO2, adjusted to pH 10 with HCl) is added and continued to stir for 10 min, and finally, condensed and refluxed at 90°C for 2 h to obtain an aqueous solution of lignin core silica shell core-shell nanoparticles, centrifuged, and dried to obtain a solid product.
[0071] The zeta potential values and particle sizes of the above-mentioned photothermal conversion materials before and after being coated with the silica shell layer were tested. The results are shown in Table 1:
[0072] Table 1 Zeta potential values and particle sizes of various photothermal conversion materials before and after coating with silica shell layer
[0073] Table 1
[0074]
[0075] Table 1 shows the zeta potential value and particle size change of each photothermal conversion material before and after coating with a silica shell. It can be seen that after coating with a silica shell, the potential value of the nanoparticles has changed. This is because after the nanoparticles are coated with a silica shell, due to the negative charge on the silica shell, the core-shell nanoparticles as a whole show a higher negative potential value than the nanoparticles. The higher the potential on the particle surface, the greater the electrostatic repulsion force between particles with the same charge, making it less likely for particles to aggregate, so the particles are more evenly dispersed in the polymer matrix. In addition, the change in particle size also well illustrates the formation of a silica shell. When the same amount of sodium metasilicate is added, a silica layer of about 15 nm is formed on the nanoparticles. The presence of the silica layer can protect the internal nanoparticles from the influence of the external environment and improve the stability of the nanoparticles.
[0076] The preparation method of the zein-pectin stabilized cinnamon essential oil Pickering emulsion used in the following comparative example is as follows: 4g zein is dissolved in 100mL ethanol (80vol%) at room temperature, and then homogenized at 10000rpm for 1min to obtain a zein nanodispersion. 2g pectin is dissolved in 100mL deionized water, heated to 70°C until completely dissolved, and centrifuged at 11000rpm for 20min to obtain a pectin solution. Subsequently, under 70°C magnetic stirring (800rmp), pectin solution is added drop by drop to the zein nanodispersion at a mass ratio of 10:4 (zein nanodispersion / pectin solution), and ethanol is evaporated for 20min. After cooling, the pH is adjusted to 3 with hydrochloric acid to obtain a zein / pectin composite colloidal particle dispersion. Then homogenized at 8000rpm for 5min. Finally, cinnamon essential oil (1:1, v / v) was added to the zein / pectin composite colloidal particle dispersion and homogenized at 14000 rpm for 4 min to obtain a zein-pectin stabilized cinnamon essential oil Pickering emulsion.
[0077] Example 1
[0078] 3g PVA, 22.5mL deionized water and 7.5mL (0.04mg / mL) gold core silica shell core-shell nanoparticle aqueous solution were added to a 100mL round-bottom flask, and then the round-bottom flask was placed in an oil bath, the temperature of the oil bath was controlled to be maintained at 90°C, and the stirring speed was 700rpm for condensation reflux reaction for 3h to obtain a composite solution; after the reaction was completed, the temperature of the composite solution was lowered to 50°C, 0.3g cinnamon essential oil β-cyclodextrin inclusion complex was added and continued to stir at 50°C for 0.5h to obtain a film-forming solution; the film-forming solution was poured into a round disposable polypropylene culture dish with a diameter of 90mm, and dried on a 35°C hot plate for 24h to obtain a photothermal and thermal response release antibacterial film.
[0079] Example 2
[0080] 3g PVA, 15mL deionized water and 15mL (0.04mg / mL) gold core silica shell core-shell nanoparticle aqueous solution were added to a 100mL round-bottom flask, and then the round-bottom flask was placed in an oil bath, the temperature of the oil bath was controlled to be maintained at 90°C, and the stirring speed was 700rpm for condensation reflux reaction for 3h to obtain a composite solution; after the reaction was completed, the temperature of the composite solution was lowered to 50°C, 0.3g cinnamon essential oil β-cyclodextrin inclusion complex was added and continued to stir at 50°C for 0.5h to obtain a film-forming solution; the film-forming solution was poured into a round disposable polypropylene culture dish with a diameter of 90mm, and dried on a 35°C hot plate for 24h to obtain a photothermal and thermal response release antibacterial film.
[0081] Example 3
[0082] 3g PVA, 10mL deionized water and 20mL (0.04mg / mL) gold core silica shell core-shell nanoparticle aqueous solution were added to a 100mL round-bottom flask, and then the round-bottom flask was placed in an oil bath, the temperature of the oil bath was controlled to be maintained at 90°C, and the stirring speed was 700rpm for condensation reflux reaction for 3h to obtain a composite solution; after the reaction was completed, the temperature of the composite solution was lowered to 50°C, 0.3g cinnamon essential oil β-cyclodextrin inclusion complex was added and continued to stir at 50°C for 0.5h to obtain a film-forming solution; the film-forming solution was poured into a round disposable polypropylene culture dish with a diameter of 90mm, and dried on a 35°C hot plate for 24h to obtain a photothermal and thermal response release antibacterial film.
[0083] Example 4
[0084] 3g PVA, 5mL deionized water and 25mL (0.04mg / mL) gold core silica shell core-shell nanoparticle aqueous solution were added to a 100mL round-bottom flask, and then the round-bottom flask was placed in an oil bath, the temperature of the oil bath was controlled to be maintained at 90°C, and the stirring speed was 700rpm for condensation reflux reaction for 3h to obtain a composite solution; after the reaction was completed, the temperature of the composite solution was lowered to 50°C, 0.3g cinnamon essential oil β-cyclodextrin inclusion complex was added and continued to stir at 50°C for 0.5h to obtain a film-forming solution; the film-forming solution was poured into a round disposable polypropylene culture dish with a diameter of 90mm, and dried on a 35°C hot plate for 24h to obtain a photothermal and thermal response release antibacterial film.
[0085] Example 5
[0086] 3 g PVA and 30 mL (0.04 mg / mL) of gold core silica shell core-shell nanoparticle aqueous solution were added to a 100 mL round-bottom flask, and then the round-bottom flask was placed in an oil bath, the temperature of the oil bath was controlled to be maintained at 90 ° C, and the stirring speed was 700 rpm for condensation reflux reaction for 3 hours to obtain a composite solution; after the reaction was completed, the temperature of the composite solution was lowered to 50 ° C, 0.3 g cinnamon essential oil β-cyclodextrin inclusion complex was added and continued to stir at 50 ° C for 0.5 hours to obtain a film-forming solution; the film-forming solution was poured into a round disposable polypropylene culture dish with a diameter of 90 mm, and dried on a 35 ° C hot stage for 24 hours to obtain a photothermal and thermal response release antibacterial film.
[0087] Example 6
[0088] 3 g PVA and 30 mL (0.1 mg / mL) of gold core silica shell core-shell nanoparticle aqueous solution were added to a 100 mL round-bottom flask, and then the round-bottom flask was placed in an oil bath, the temperature of the oil bath was controlled to be maintained at 90 ° C, and the stirring speed was 700 rpm for condensation reflux reaction for 3 hours to obtain a composite solution; after the reaction was completed, the temperature of the composite solution was lowered to 50 ° C, 0.3 g cinnamon essential oil β-cyclodextrin inclusion complex was added and continued to stir at 50 ° C for 0.5 hours to obtain a film-forming solution; the film-forming solution was poured into a round disposable polypropylene culture dish with a diameter of 90 mm, and dried on a 35 ° C hot stage for 24 hours to obtain a photothermal and thermal response release antibacterial film.
[0089] Example 7
[0090] 3 g PVA and 30 mL (0.04 mg / mL) of gold core silica shell core-shell nanoparticle aqueous solution were added to a 100 mL round-bottom flask, and then the round-bottom flask was placed in an oil bath, the temperature of the oil bath was controlled to be maintained at 90 ° C, and the stirring speed was 700 rpm for condensation reflux reaction for 3 hours to obtain a composite solution; after the reaction was completed, the temperature of the composite solution was lowered to 50 ° C, 0.15 g cinnamon essential oil β-cyclodextrin inclusion complex was added and continued to react at 50 ° C for 0.5 h to obtain a film-forming solution; the film-forming solution was poured into a round disposable polypropylene culture dish with a diameter of 90 mm, and dried on a 35 ° C hot stage for 24 hours to obtain a photothermal and thermal response release antibacterial film.
[0091] Example 8
[0092] 3 g PVA and 30 mL (0.04 mg / mL) of gold core silica shell core-shell nanoparticle aqueous solution were added to a 100 mL round-bottom flask, and then the round-bottom flask was placed in an oil bath, the temperature of the oil bath was controlled to be maintained at 90 ° C, and the stirring speed was 700 rpm for condensation reflux reaction for 3 hours to obtain a composite solution; after the reaction was completed, the temperature of the composite solution was lowered to 50 ° C, 0.9 g cinnamon essential oil β-cyclodextrin inclusion complex was added and continued to stir at 50 ° C for 0.5 hours to obtain a film-forming solution; the film-forming solution was poured into a round disposable polypropylene culture dish with a diameter of 90 mm, and dried on a 35 ° C hot stage for 24 hours to obtain a photothermal and thermal response release antibacterial film.
[0093] Example 9
[0094] 0.6 g pectin, 10 mL deionized water and 20 mL (0.04 mg / mL) gold core silica shell core-shell nanoparticle aqueous solution were added to a 100 mL round-bottom flask, and then the round-bottom flask was placed in an oil bath, the temperature of the oil bath was controlled to be maintained at 75 ° C, and the stirring speed was 700 rpm for condensation reflux reaction for 2 hours, and then 0.18 g glycerol was added, and the stirring reaction was continued at 75 ° C for 2 hours to obtain a composite solution; after the reaction was completed, the temperature of the composite solution was lowered to 50 ° C, 0.3 g cinnamon essential oil β-cyclodextrin inclusion complex was added, and the stirring reaction was continued at 50 ° C for 0.5 hours to obtain a film-forming solution; the film-forming solution was poured into a round disposable polypropylene culture dish with a diameter of 90 mm, and dried on a 35 ° C hot stage for 24 hours to obtain a photothermal and thermal response release antibacterial film.
[0095] Example 10
[0096] In a 100-mL round-bottom flask, 0.3 g of chitosan, 0.075 g of glycerol, 10 mL of a 3 wt% acetic acid aqueous solution and 20 mL (0.04 mg / mL) of a gold core silica shell core-shell nanoparticle aqueous solution were added, and the mixture was stirred at 900 rpm for 12 h at room temperature to obtain a composite solution. After the reaction was completed, 0.3 g of cinnamon essential oil β-cyclodextrin inclusion complex was added and the reaction was continued for 0.5 h to obtain a film-forming solution. The film-forming solution was poured into a circular disposable polypropylene culture dish with a diameter of 90 mm, and dried on a hot plate at 35°C for 24 h to obtain a photothermal and thermal responsive release antibacterial film.
[0097] Embodiment 11
[0098] 1.5 g of polylactic acid, 0.8 mg of gold core silica shell core-shell nanoparticles and 30 mL of dichloromethane were added to a 100 mL round-bottom flask, and the mixture was stirred at 700 rpm by magnetic stirring at room temperature for 3 h to obtain a composite solution; then 0.3 g of cinnamon essential oil β-cyclodextrin inclusion complex was added and the reaction was continued for 0.5 h to obtain a film-forming solution; the film-forming solution was poured into a round disposable polypropylene culture dish with a diameter of 90 mm, and dried on a hot plate at 35°C for 24 h to obtain a photothermal and thermal responsive release antibacterial film.
[0099] Example 12
[0100] In a 100-mL round-bottom flask, 0.6 g of carboxymethyl cellulose, 10 mL of deionized water and 20 mL (0.04 mg / mL) of gold core silica shell core-shell nanoparticle aqueous solution were added, and then mechanically stirred at 400 rpm for 0.5 h at room temperature to obtain a composite solution; then 0.3 g of cinnamon essential oil β-cyclodextrin inclusion complex was added and the stirring reaction was continued for 0.5 h to obtain a film-forming solution; the film-forming solution was poured into a round disposable polypropylene culture dish with a diameter of 90 mm, and dried on a hot plate at 35°C for 24 h to obtain a photothermal and thermal responsive release antibacterial film.
[0101] Embodiment 13
[0102] 0.3 g of chitosan was dissolved in 30 mL of 1 wt% acetic acid aqueous solution, and stirred at 50 ° C (250 rpm) for 2 h to obtain a chitosan solution; 3 g of polyvinyl alcohol, 20 mL of deionized water and 40 mL (0.04 mg / mL) of gold core silica shell core-shell nanoparticle aqueous solution were mixed, and stirred (700 rpm) for condensation reflux reaction at 90 ° C for 3 h to obtain a polyvinyl alcohol solution; then the polyvinyl alcohol solution and the chitosan solution were mixed evenly by mechanical stirring (600 rpm) to obtain a composite solution; then 0.45 g of cinnamon essential oil β-cyclodextrin inclusion complex was added and the stirring reaction was continued for 0.5 h to obtain a film-forming solution; the film-forming solution was poured into a circular disposable polypropylene culture dish with a diameter of 90 mm, and dried on a hot plate at 35 ° C for 24 h to obtain a photothermal and thermal response release antibacterial film.
[0103] Embodiment 14
[0104] Same as Example 3, except that 20 mL (0.04 mg / mL) of gold core silica shell core-shell nanoparticle aqueous solution was replaced with 20 mL (0.2 mg / mL) of silver core silica shell core-shell nanoparticle aqueous solution.
[0105] Embodiment 15
[0106] Same as Example 3, except that 20 mL (0.04 mg / mL) of gold core silica shell core-shell nanoparticle aqueous solution was replaced with 20 mL (0.6 mg / mL) of manganese oxide core silica shell core-shell nanoparticle aqueous solution.
[0107] Example 16
[0108] Same as Example 3, except that 20 mL (0.04 mg / mL) of gold core silica shell core-shell nanoparticle aqueous solution was replaced with 20 mL (60 mg / mL) of lignin core silica shell core-shell nanoparticle aqueous solution.
[0109] Comparative Example 1
[0110] 3 g PVA, 10 mL deionized water and 20 mL (0.04 mg / mL) gold core silica shell core-shell nanoparticle aqueous solution were added to a 100 mL round-bottom flask, and then the round-bottom flask was placed in an oil bath, the temperature of the oil bath was controlled to be maintained at 90 ° C, and the stirring speed was 700 rpm for condensation reflux reaction for 3 hours to obtain a film-forming solution; the film-forming solution was poured into a round disposable polypropylene culture dish with a diameter of 90 mm, and dried on a hot plate at 35 ° C for 24 hours to obtain an antibacterial film.
[0111] Comparative Example 2
[0112] 3 g PVA and 30 mL deionized water were added to a 100 mL round-bottom flask, and then the round-bottom flask was placed in an oil bath. The temperature of the oil bath was controlled to be maintained at 90 ° C. The stirring speed was 700 rpm and the reaction was condensed and refluxed for 3 hours to obtain a composite solution. After the reaction was completed, the temperature of the composite solution was lowered to 50 ° C, 0.3 g cinnamon essential oil β-cyclodextrin inclusion complex was added, and the reaction was continued at 50 ° C for 0.5 hours to obtain a film-forming solution. The film-forming solution was poured into a round disposable polypropylene culture dish with a diameter of 90 mm, and dried on a 35 ° C hot stage for 24 hours to obtain an antibacterial film.
[0113] Comparative Example 3
[0114] 3 g PVA and 30 mL deionized water were added to a 100 mL round-bottom flask, and then the round-bottom flask was placed in an oil bath, and the temperature of the oil bath was controlled to be maintained at 90°C. The stirring speed was 700 rpm, and the reaction was condensed and refluxed for 3 hours to obtain a film-forming solution; the film-forming solution was poured into a circular disposable polypropylene culture dish with a diameter of 90 mm. After drying on a hot plate at 35°C for 24 hours, a film was obtained.
[0115] Comparative Example 4
[0116] Commercial ordinary PE cling film, thickness is 0.2mm.
[0117] Comparative Example 5
[0118] 3g PVA, 10mL deionized water and 20mL (0.04mg / mL) gold core silica shell core-shell nanoparticle aqueous solution were added to a 100mL round-bottom flask, and then the round-bottom flask was placed in an oil bath, the temperature of the oil bath was controlled to be maintained at 90°C, and the stirring speed was 700rpm for condensation reflux reaction for 3h to obtain a composite solution; after the reaction was completed, the temperature of the composite solution was lowered to 50°C, 0.3g zein-pectin nanoparticle-stabilized cinnamon essential oil Pickering emulsion was added, and the reaction was continued at 50°C for 10min to obtain a film-forming solution; the film-forming solution was poured into a round disposable polypropylene culture dish with a diameter of 90mm, and dried on a 35°C hot stage for 24h to obtain a photothermal and thermal response release antibacterial film.
[0119] Test Example 1
[0120] Film mechanical properties test
[0121] Test method: A universal tensile testing machine (SUST, China) was used for testing. The test sample size was 2×35×0.2mm. 3 The dumbbell-shaped specimens were used. The sample fixtures were spaced 15 mm apart, the test speed was 10 mm / min, each sample was tested 6 times in parallel, and the final result was averaged.
[0122] Table 2 shows the mechanical tensile test results of the films prepared in Examples 1-16 of the present invention and Comparative Examples 1-3.
[0123] Table 2
[0124]
[0125]
[0126] As can be seen from Table 2, in Examples 1-6, as the addition amount of gold core silica shell core-shell nanoparticles increases from 0.001-0.01%, the elongation at break of the film shows a gradual increasing trend, and the strength of the film also gradually increases but the change trend is not large; in Examples 5, 7 and 8, the addition amount of natural plant essential oil cyclodextrin inclusion complex is changed from 0.5-3% while fixing the addition amount of gold core silica shell core-shell nanoparticles, the elongation at break of the film shows a gradual increasing trend, and the strength of the film also shows an increasing trend.
[0127] By comparing with control examples 1-3, it can be seen that the addition of gold core silica shell core-shell nanoparticles and natural plant essential oil cyclodextrin inclusion complexes will slightly reduce the mechanical properties of the polyvinyl alcohol film. However, since the polyvinyl alcohol film itself has excellent mechanical properties, the addition of gold core silica shell core-shell nanoparticles and natural plant essential oil cyclodextrin inclusion complexes does not have much effect on the mechanical properties of the film. The reduction is within an acceptable range, and the film as a whole still has excellent mechanical properties.
[0128] In addition, in addition to exploring the mechanical properties of films prepared with polyvinyl alcohol as the film-forming substrate, the embodiments of the present invention also explore the mechanical properties of films prepared with other different film-forming substrates and different photothermal conversion materials. It can be seen from Examples 9-16 that after adding gold core silica shell core-shell nanoparticles and natural plant essential oil cyclodextrin inclusion complexes to each film-forming substrate, the mechanical properties of the prepared films are within the reasonable range of the mechanical properties of films prepared with a single film-forming substrate; in the case of the same film-forming substrate, different photothermal conversion materials have little effect on the mechanical properties of the film.
[0129] Test Example 2
[0130] Thin film photothermal conversion performance test
[0131] Test method: Irradiate the film with an infrared laser of 808nm wavelength, and monitor and record the temperature change of the film over time with an infrared thermal imager.
[0132] Figure 1 The photothermal conversion experimental results of the films prepared in Examples 1-6 of the present invention are shown in the figure. As shown in the figure, in Examples 1-6, as the amount of gold core silica shell core-shell nanoparticles added increases from 0.001% to 0.01%, the photothermal conversion performance of the film is also continuously improved, and the maximum temperature that the film can reach for photothermal conversion rises from 40±2℃ to 107±1℃, and the films of Examples 1-6 can reach the maximum temperature within 1 minute, which proves that the film has good photothermal conversion performance;
[0133] Figure 2 The photothermal conversion experimental results of the films prepared in Examples 7-8 and Control Examples 1-3 show that from Control Examples 2 and 3, without the addition of gold core silica shell core-shell nanoparticles, the films do not have the photothermal conversion performance, while the films of Examples 7 and 8 have the same photothermal conversion performance when the same content of gold core silica shell core-shell nanoparticles is added. In addition, by comparing the results of Example 2 and Control Example 1 as well as Example 5 and Examples 7-8, it can be seen that the addition of natural plant essential oil cyclodextrin inclusion complex does not affect the photothermal performance of the film.
[0134] Figure 3The photothermal conversion experimental results of the films prepared in Examples 14-16 are shown. The photothermal conversion materials of the three examples are replaced on the basis of Example 3. In this test example, the photothermal conversion performance of different photothermal materials is explored based on the same photothermal conversion temperature. Among them, the gold core silica shell core-shell nanoparticles have the least addition amount, followed by silver core silica shell core-shell nanoparticles and manganese oxide core silica shell core-shell nanoparticles. The largest addition amount is lignin core silica shell core-shell nanoparticles. It can be seen that the gold core silica shell core-shell nanoparticles have the best photothermal conversion performance. When the same photothermal conversion temperature can be achieved, the addition amount is much less than that of other materials. The less the material added, the less the amount migrating from the film, and the higher the safety of the film.
[0135] Test Example 3
[0136] Film antibacterial performance test
[0137] Test method: The coating plate method was used to test the inhibition rate of the film against Escherichia coli and Staphylococcus aureus; specifically, the film was first cut into discs with a diameter of 5 mm, 10 μL of bacterial suspension of a specific concentration was dropped on the discs, the experimental group was illuminated with 808 nm near-infrared light for 5 minutes, and the control group was directly placed for 5 minutes and then rinsed with 400 μL PBS buffer solution. Finally, 100 μL of the dilution was added to the culture medium and placed in a biochemical incubator for 12 hours.
[0138] After proving that the film has excellent photothermal conversion performance, considering the impact of high temperature on food, the higher the temperature, the easier it is to affect the quality of food; the present invention selects Example 3 with a photothermal temperature in the range of 68-70°C as the optimal group for the next antibacterial experiment. Example 3 can maximize the effect of photothermal sterilization and promoting the release of essential oils without affecting the quality of food. Staphylococcus aureus is used as a Gram-positive bacteria and Escherichia coli is used as a Gram-negative bacteria to explore the antibacterial effect of the film; Figure 4 , 5 , 6, and 7 are the antibacterial test results of the films prepared in Example 3 of the present invention and Comparative Examples 1-3. Figure 4 and Figure 5 From the number of colonies on the culture dish, it can be seen that the pure PVA film of Control Example 3 has no antibacterial effect, while the PVA film prepared in Control Example 2 with only essential oil inclusion compound added has a certain antibacterial effect on Staphylococcus aureus, but has no antibacterial effect on Escherichia coli; this shows that the cinnamon essential oil used in the present invention has an antibacterial effect on Staphylococcus aureus, but is not applicable to Escherichia coli, which also verifies the problem that a single antibacterial agent cannot achieve broad-spectrum sterilization in diffusion sterilization.
[0139] In contrast, the films containing gold core silica shell core-shell nanoparticles prepared in Example 3 and Control Example 1 showed significant bactericidal effects on both bacteria under 808nm near-infrared light illumination, but the film of Control Example 1 did not completely kill Staphylococcus aureus, while the film of Example 3 achieved complete killing of both bacteria. This is mainly because Escherichia coli is more sensitive to temperature and can be completely killed when the ambient temperature reaches 70°C, while Staphylococcus aureus is relatively more heat-resistant and usually requires a temperature of more than 80°C to be completely killed; in addition, in the absence of light, Example 3 showed a certain bactericidal effect on Staphylococcus aureus due to the simultaneous incorporation of natural essential oil inclusion compounds, while Control Example 1 did not have a bactericidal effect in the absence of light.
[0140] Based on the results of the above antibacterial experiments, it can be concluded that the films of Control Example 2 in which only the natural plant essential oil inclusion compound was added and Control Example 1 in which only the gold core silica shell core-shell nanoparticles were added could not achieve complete sterilization. However, the present invention, by co-incorporating the natural plant essential oil inclusion compound and the gold core silica shell core-shell nanoparticles into the PVA film, achieved an antibacterial rate of 100% against Staphylococcus aureus and Escherichia coli under infrared light.
[0141] Test Example 4
[0142] Essential oil thermal response release test
[0143] Test method: Take two films of a specific size on the same film and soak them in a glass reagent bottle filled with 95 vol% ethanol. Then place the glass reagent bottle in a water bath at room temperature and 70°C respectively. Take out 2 mL of solution from the bottle at specific intervals. Test the ultraviolet spectrum of the taken solution. Calculate the content of cinnamon essential oil in the solution based on the characteristic peak absorbance of cinnamon essential oil at 285 nm and the concentration standard curve of cinnamon essential oil in ethanol to infer the amount of cinnamon essential oil released from the film. After the test, pour the solution back into the glass bottle.
[0144] Specifically, in order to prove that increasing the temperature will accelerate the release of cinnamon essential oil from cyclodextrin, two films of the same size were taken from the film prepared in Example 3 and placed in glass bottles filled with 95 vol% ethanol, respectively. The control group was kept at room temperature, while the experimental group was first placed in 70°C hot water for 5 minutes, then placed at room temperature, and then placed in 70°C hot water again for 5 minutes every two hours, and the cycle was repeated until the test was completed. The test results are shown in Figure 2. Figure 8As shown, after heating for 5 minutes, the content of cinnamon essential oil in the solution of the experimental group was about 2.5 times that of the control group placed at room temperature, and each subsequent heating for 5 minutes increased the content of cinnamon essential oil in the solution significantly, proving that the method of the present invention for promoting the accelerated release of cinnamon essential oil from cyclodextrin by heating is effective and has a significant effect.
[0145] The present invention also explores the effect of different embedding materials on thermal response release. A piece of film of the same size was taken from the film prepared in Example 3 and Comparative Example 5, and then placed in a glass bottle filled with 95 vol% ethanol. Both sets of films were first placed in 70°C hot water for 5 minutes, and then placed at room temperature. The UV spectrum was then measured every two hours, and the cycle was repeated until the test was completed. The test results are as follows Fig. 9 As shown, after soaking in hot water at 70°C for 5 minutes, the release rate of cinnamon essential oil in the film of comparative example 5 quickly rose to 60%, while the release rate of cinnamon essential oil in the film of example 3 rose steadily to 30%; then the release rate of cinnamon essential oil in the film of comparative example 5 reached more than 90% in the 6th hour, while the release rate of cinnamon essential oil in the film of example 3 continued to rise steadily within 12 hours. From the above experimental results, it can be analyzed that after the temperature is increased, the cinnamon essential oil stabilized by zein-pectin nanoparticles releases a large amount of cinnamon essential oil in a short time because the protein pectin substances are easily denatured by high temperature, which greatly weakens the continuous antibacterial effect, while cyclodextrin is relatively more resistant to high temperature, so it can still maintain activity after high temperature and continuously and stably release cinnamon essential oil.
[0146] Application Example 1
[0147] Application experiment of beef preservation
[0148] Experimental method: Fresh beef was selected as the preservation object, wrapped with film, sealed with sealant, and then irradiated with 808nm near-infrared light for 5 minutes. At the same time, unpackaged beef and beef packaged with commercial PE plastic wrap were used as controls. All samples were placed in an indoor environment of 25±1℃ for 5 days, and three groups of samples were taken on the second and fifth days for relevant index tests.
[0149] In addition to providing a method for preparing the above-mentioned antibacterial film, the present invention also provides an example of applying the antibacterial film of the present invention to food packaging. Specifically, in this application example, the antibacterial film of the present invention is applied to the fresh-keeping packaging of beef. Specifically, the films prepared in reference examples 1-3, the commercial PE fresh-keeping film of reference example 4, and the film prepared in embodiment 3 are used to encapsulate the beef. At the same time, a blank control group is set up, and the samples of reference example 1 and embodiment 3 are irradiated with 808nm near-infrared light for 5 minutes, and the remaining groups are not subjected to light treatment. Finally, the samples of each group are uniformly placed in an indoor environment of 25±1℃ for 5 days, and after sampling and homogenization on the 2nd and 5th days, the homogenate is diluted and coated on a culture dish for culture; the colony diagram of each group of samples is as follows Fig.10 , 11 As shown, combined Fig.12 From the total colony count graph, it can be concluded that after 2 days of storage, the total colony counts of Control Examples 1-3 and Example 3 were nearly half of those of the blank group and Control Example 4, and the total colony count of Control Example 4 was more than that of the blank group. Comparing the total colony counts of Control Examples 1-3 and Example 3, the total colony count of beef samples subjected to synergistic antibacterial release by photothermal and essential oil was less than that of the simple PVA film, single photothermal and single essential oil antibacterial.
[0150] On the 5th day, the total number of colonies in the blank group and control example 4 increased sharply, the total number of bacteria in the blank group increased by about 1 times, and the total number of bacteria in the PE plastic wrap group increased by about 3 times. In comparison, the total number of colonies in control examples 1-3 and example 3 on the 5th day increased less than that on the 2nd day, among which the total number of colonies in control example 3 was the highest, followed by control example 2, control example 1 and example 3.
[0151] Combining the above-mentioned total colony count data, firstly, by comparing the total colony count on the second day, it can be seen that the total colony counts of Control Examples 1-3 and Example 3 are less than that of the blank control group, which indicates that the film wrapping blocks the invasion of external bacteria to a certain extent, and the total colony count of the commercial PE cling film is more than that of the blank control group, which may be because the commercial PE cling film has poor water permeability, and the moisture exuded from the beef during storage cannot pass through the cling film, resulting in continuous accumulation of moisture in the environment sealed by the cling film, which aggravates the growth rate of bacteria; after adding the antibacterial agent, the total colony counts of Control Examples 1-2 and Example 3 are less than that of Control Example 3, and after being treated with light, the total colony counts of Example 3 and Control Example 1 are less than that of Control Example 2 in which only the essential oil inclusion complex is added, from which it can be inferred that the effect of photothermal sterilization is better than that of essential oil sustained-release sterilization, and further, the total colony count of Example 3 is significantly less than that of Control Example 1, which proves that the synergistic sterilization effect of photothermal and essential oil release is better than that of single photothermal sterilization;
[0152] Secondly, comparing the total colony count on the 5th day, the growth rate of the total colony count in Control Example 2 and Example 3 is lower than that in Control Example 1. It can be inferred that during the storage process, the film can continue to slowly release the essential oil, effectively inhibiting the growth of bacteria in the sample. Therefore, the total colony count on the 5th day increased less than that on the 2nd day, proving that the slowly released essential oil has a sustained antibacterial effect.
[0153] In addition to the total bacterial count, volatile basic nitrogen (TVB-N) is also often used to reflect food spoilage, such as Fig.13 As shown, compared with the 0th day, the TVB-N of each group of samples increased after 2 days of placement, among which the increase of TVB-N in the control example 4 and the blank group was larger, and the TVB-N values of the PE cling film group and the blank group exceeded the maximum limit of 15 mg / 100 g specified in GB 2707-2016 "National Food Safety Standard for Fresh (Frozen) Livestock and Poultry Products"; the average TVB-N values of the control examples 1-3 were equal (14.78 mg / 100 g) and very close to the maximum limit of 15 mg / 100 g, while the increase in Example 3 was the smallest and the average TVB-N value was lower than 15 mg / 100 g;
[0154] On the 5th day, the TVB-N of the blank group and the control example 4 samples increased significantly, and the increase in the PE plastic wrap group was more rapid, indicating that the degree of corruption of the samples in this group was very serious. Compared with the blank group and the PE plastic wrap group, the increase in TVB-N of the other sample groups was not large, but except for the TVB-N average value of Example 3 which was still below 15 mg / 100 g, the TVB-N average values of the other groups of samples exceeded 15 mg / 100 g, exceeding the maximum limit specified in GB 2707-2016, indicating that the beef samples had undergone unacceptable corruption.
[0155] The embodiments described are only descriptions of the preferred modes of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A photothermal and thermal response release antibacterial film, characterized in that: The raw materials include a solvent and the following components in amounts as percentage by mass of the solvent: 1-10% of a film-forming substrate, 0.5-3% of a natural plant essential oil inclusion compound, 0.001-4% of a photothermal conversion substance and 0-0.6% of glycerol.
2. The photothermal and thermal response release antibacterial film according to claim 1, characterized in that: The film-forming substrate is one or more of polyvinyl alcohol, chitosan, carboxymethyl cellulose, polylactic acid and pectin.
3. The photothermal and thermal response release antibacterial film according to claim 1, characterized in that: The natural plant essential oil inclusion compound consists of natural plant essential oil and cyclodextrin.
4. The photothermal and thermal response release antibacterial film according to claim 3, characterized in that: The natural plant essential oil is one or more of cinnamon essential oil, thymol essential oil, oregano essential oil, eugenol essential oil, neroli essential oil, peppermint essential oil and tea tree essential oil.
5. The photothermal and thermal response release antibacterial film according to claim 1, characterized in that: The photothermal conversion material is one or more of gold nanoparticles, silver nanoparticles, manganese oxide nanoparticles and lignin nanoparticles.
6. The photothermal and thermal response release antibacterial film according to claim 5, characterized in that: The surface of the light-to-heat conversion material is coated with a silicon dioxide shell layer.
7. The photothermal and thermal response release antibacterial film according to claim 1, characterized in that: The solvent is one or more of water, acetic acid and dichloromethane.
8. The method for preparing the photothermal and thermal response release antibacterial film according to any one of claims 1 to 7, characterized in that: The following steps are involved: Weigh each raw material according to the mass percentage composition of the raw materials, mix the other raw materials except the natural plant essential oil inclusion compound to obtain a composite solution; add the natural plant essential oil inclusion compound to the composite solution to obtain a film-forming liquid; pour the film-forming liquid into a vessel for film formation, dry it, and obtain the photothermal and thermal response release antibacterial film.
9. Use of the photothermal and thermal responsive release antibacterial film as claimed in any one of claims 1 to 7 in food packaging.
Citation Information
Patent Citations
Nuclear shell structure intelligent disinfectant containing silver
CN101816302A
Active packaging film based on essential oil / beta-cyclodextrin inclusion compound and preparation method for active packaging film
CN102585412A
Silica-coated silver core composite particles and their preparation method and use
CN102660160A
Antibacterial packaging film and preparation method thereof
CN104277249A
Cited By
Preparation method of antibacterial and antiseptic food packaging material
CN120040813A
Method for preparing antibacterial and antiseptic food packaging material
CN120040813B
